Short stature and melanocytic nevi in a girl with ARID1B-related Coffin-Siris syndrome: a case report - Dong-Ying Tao; Huan-Hong Niu; Jing-Jing Zhang; Hui-Qin Zhang; Ming-Hua Zeng; Sheng-Quan Cheng (BMC, 2022)
Abstract Background Coffin-Siris syndrome (CSS) is a rare autosomal dominant disorder characterized by intellectual disability, developmental delay, and characteristic facial features. Few patients with cutaneous phenotype in this rare syndrome have been reported. Case presentation Herein, we describe a 12-year-old Chinese girl diagnosed with CSS, who was referred to our hospital because of intellectual disability and short stature. Prominent characteristics of the cutaneous system were observed: (1) A congenital giant nevus from the left frontal and temporal regions to the entire left scalp; and (2) multiple melanocytic nevi on the face and trunk. Whole exome sequencing revealed a novel heterozygous variant in the ARID1B gene. Recombinant human growth hormone (rhGH) was given for short stature, and resulted in significantly improved height. No enlargement or malignant transformation of nevi occurred within 4 years of follow-up. Conclusion The symptoms in cutaneous system is noteworthy,which may be a neglected phenotype in CSS.The therapeutic response of growth hormone is effective in this patient and no tumor related signs were found.